Robotic ultrasound trajectory planning for volume of interest coverage - Graumann, Christoph; Fuerst, Bernhard; Hennersperger, Christoph; Bork, Felix; Navab, Nassir (Proceedings - IEEE International Conference on Robotics and Automation, 2016)
Medical robotic ultrasound offers potential to assist interventions, ease long-term monitoring and reduce operator dependency. Various techniques for remote control of ultrasound probes through telemanipulation systems have been presented in the past, however not exploiting the potential of fully autonomous acquisitions directly performed by robotic systems. In this paper, a trajectory planning algorithm for automatic robotic ultrasound acquisition under expert supervision is introduced. The objective is to compute a suitable path for covering a volume of interest selected in diagnostic images, for example by prior segmentation. A 3D patient surface point cloud is acquired using a depth camera, which is the sole prerequisite besides the volume delineation. An easily parameterizable path function generates single or multiple parallel scan trajectories capable of dealing with large target volumes. A spline is generated through the preliminary path points and is transferred to a lightweight robot to perform the ultrasound scan using an impedance control mode. The proposed approach is validated via simulation as well as on phantoms and on animal viscera.
CRIS-Team Scopus Importer:2023-03-08